การเมืองในสถาปัตยกรรมรัฐสภาไทย - อรณัฐ ปิยะจารุวัฒน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
This research focuses on the architecture of the "Sappaya Saphasathan, including other Thai National Assembly Buildings, and their political meanings. The objective of this study is to understand architecture through the political history of the National Assembly Buildings, both Parliament and Senate, and its political meanings. This research uses qualitative methods by looking at documents and evidence related to the history and style of the constructions, conceptual designs, and sites.The findings point out that, firstly, most of the governmental offices, especially Thai Parliament Buildings, have significant political implications in the ways in which they convey asymmetric power relations between the state and people through designs and architectural styles.Secondly, the research highlights the history of Parliament buildings that are focal points of political incidents. Ananta Samakhom Throne Hall, designed and decorated to host royal guests, cherished with great historical moments of Siamese royals, became the place to hold the royal constitution granting ceremony. The throne hall is the site of transition from absolute monarchy to a constitutional monarchy. While the second parliament building was built under a long period of military rules. Thus, its modern architectural style focused on modern architecture to celebrate Thailand as a modern country with ‘blooming democratic values’.Lastly, Sappaya Saphasathan is designed under the concept that the National Assembly should be a moral space to contemplate politics without conflicts. The design based on Buddhist and Hindu concepts of cosmology dividing the Sun and Moon under the three worlds. On the top of the building crowned with a golden Julamanee pagoda, and placed the Siam Devadhiraja, the most supreme and holy guardian of ancient Siamese state inside the pagoda. All of the concepts and designs are meant to reconstruct the morale and courage of Thais for the architecture team believed that Thailand has been in crisis because Thais have lost their moral virtues. So the Sumeru mountain, a center of power of the Thai state, is meant to remind the legislators of their duty for the whole nation under the patronage of the Siamese holy spirit. But on the other hand, the ancient guardian also represents the monarchy as the highest order in Thai cosmology over western democratic values.